Cultos militares y espacios sagrados en el campamento de la legio VII gemina en León - Morillo Cerdán, Ángel (Gerión. Revista de Historia Antigua, 2009)
Starting from the epigraphic evidences found in León, mostly reused in the Tetrarchic wall, about the Roman military cults, we draw a scene of the religious beliefs in the camp of the legio VII gemina, where goddess like Diana, the Nymphs and the Genius of the seventh legion, as well as that of the emperor, hold a prominent position. Together with them, other divinities are stated, that is the case of Mars, documented in León for the first time. Taking into account the place were those plaques were located within the wall and some topographic, literary and archaeological evidences, we proposed some hypothesis about the possible location of several sacred spaces in certain areas of the camp and its surroundings.